Sources of convergence in the European Union and Portugal - Pontes, José Pedro (2000)
he paper surveys the main trends of per capita income convergence in the European Union. It stresses that income disparities have ceased to diminish across the European regions since 1980, although convergence between countries has continued in this period. Income levels have diverged inside each country in a weak sense with two exceptions. Theoretical forces behind income convergence are analized by means of the decomposition of per capita income in labor productivity and employment rate and applied to the stylized facts outlined above. The case of Portugal is regarded as an atypical one, since the country has converged as a whole to the European average and among its regions. The flexibility of the Portuguese labor market is regarded as the main factor behind this performance. However, the limited convergence of labor productivity bounds the expected future performance of the Portuguese economy.